2006
DOI: 10.1074/jbc.m602579200
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Neurotrophic Factors on Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL)-mediated Apoptosis of Murine Adrenal Chromaffin Cell Line tsAM5D

Abstract: We previously established the murine adrenal chromaffin cell line tsAM5D, which was immortalized with the temperaturesensitive simian virus 40 large T-antigen. tsAM5D cells have the capacity to differentiate into neuron-like cells in response to neurotrophic factors when the culture temperature is shifted from 33 to 39°C. In this model system, the temperature shift in the absence of neurotrophic factors led to cell death. Hoechst staining analysis revealed that typical apoptotic nuclei appeared in a time-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…The expression of CD95 on DC is dependent on DC maturation as it was shown that 14% of mouse BMDC expressed CD95 at day 8 of cultivation [57] which is in accordance with the CD95 expression (13%) of DC used in this study. The TNF-related apoptosis-inducing ligand (TRAIL) mainly induces apoptosis in transformed (tumor) cells [58,59] sparing healthy, non-transformed cells [60][61][62]. However, some reports indicate that TRAIL may also trigger cell death in primary cells, i.e., mouse thymocytes [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD95 on DC is dependent on DC maturation as it was shown that 14% of mouse BMDC expressed CD95 at day 8 of cultivation [57] which is in accordance with the CD95 expression (13%) of DC used in this study. The TNF-related apoptosis-inducing ligand (TRAIL) mainly induces apoptosis in transformed (tumor) cells [58,59] sparing healthy, non-transformed cells [60][61][62]. However, some reports indicate that TRAIL may also trigger cell death in primary cells, i.e., mouse thymocytes [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was earlier reported that, in some of tsSV40T-immortalized cell lines, the upshift to the nonpermissive temperature not only induces growth arrest but also causes apoptotic cell death Yanai and Obinata, 1994;Zheng et al, 1994;Guenal et al, 1997;Walther et al, 1999;Tavelin et al, 1999;Wade et al, 1999). Because p53 has the ability to induce apoptotic cell death (Evan et al, 1998;Gottlieb et al, 1998), it has been suggested that the apoptotic death of tsSV40T-immortalized cells upon temperature upshift reflects the biological activity of p53 released from its complex with the thermolabile T-antigen (Murata et al, 2006;Yanai and Obinata, 1994;Zheng et al, 1994). GDNF and neurturin individually promoted the tsAM5NE cell survival and acted to cause the cells to differentiate into neuron-like cells.…”
Section: Figurementioning
confidence: 99%
“…TRAIL-neutralizing antibody has been shown previously to effectively inhibit apoptosis in different models (Cantarella et al , 2010; Murata et al , 2006). Treatment of the follicles with TRAIL-neutralizing antibody alone did not result in any significant changes in keratinocyte proliferation or apoptosis, while expression of TRAIL in the hair matrix was markedly decreased suggesting for inhibition of TRAIL activity (data not shown).…”
Section: Resultsmentioning
confidence: 99%